Kualitas Organoleptik, Oksidasi Lemak dan Total Bakteri Sui Wu’u Yang Diolah Dari Otot Paha Belakang dan Diberi Level Tepung Jagung Yang Berbeda - Taek, Paskalius; E. Malelak, Gemini; M. Sipahelut, Geetruida; Sulmiyati, Sulmiyati (Journal of Comprehensive Science, 2024)
Pork has an important role in the lives of the people of East Nusa Tenggara (NTT), both as a source of animal protein and in cultural and social contexts. Traditional processed products such as Sui Wu'u from Bajawa are examples of pork preservation that has been passed down from generation to generation through the practice of local wisdom. The preservation process using natural ingredients such as cornstarch and salt not only extends the shelf life, but also improves the sensory quality as well as maintains the microbiological and physicochemical qualities of the meat. The addition of cornmeal which is rich in antioxidants and fiber and salt as natural preservatives, helps inhibit the growth of pathogenic microbes and maintains the taste of the product. Nonetheless, the curing process needs to pay attention to various factors such as raw materials, curing methods, and storage temperatures to ensure the quality and safety of the final product. The purpose of this study was to determine the organoleptic quality, fat oxidation and total bacteria in sui wu'u. The design used was a completely randomized design (CRD) consisting of 3 treatments 4 replicates of the addition of corn flour consisting of P1 = 500 g, P2 = 1000 g, P3 = 1,500 g. The parameter measured were: organoleptic quality (color, aroma, taste, and tenderness), fat oxidation and total bacteria. The data of organoleptics were analysed witk Kuakall-Wallis test whereas fat oxidation and total bacteria were analyzed with ANOVA. The results showed that organoleptic quality (color, aroma, taste, and tenderness) and total bacteri were same  (P>0.05) whereas fat oxidation decreased as the level of corn starch increased.  It can be concluded that given corn starch coulg retard the fat oxidation.